Pengaruh Kualitas Produk, Harga dan Brand Ambassador terhadap Keputusan Pembelian Produk Lipstik pada Madame Gie Official Shop di Marketplace Shopee - Ellen Indriati; Anggie Veronica; Mentiana Sibarani (Program Studi Manajemen Universitas Muhadi Setiabudi, 2022)
Lifestyle factors that require humans to look beautiful and perfect make cosmetics one of the things that women must have. Even though it’s still a pandemic, the demand for cosmetic products is increasing, this is evidenced by the increasing sales of cosmetic products every year. Especially now that shopping is easier because it is supported by marketplace, one of them is Shopee which is in great demand by women and the average person who likes Shopee is the millennial generation and Z generation. Many local cosmetic products in Indonesia are starting to appear every year and flood the homeland market, one of them is Madame Gie who was born with a beautiful economic main character. In 2015 lipstick became one of the must have cosmetic items for women. As a newcomer, Madame Gie managed to become the top lip cosmetic brand in Shopee. Sometimes Madame Gie also participates in Shopee flash sales to increase sales. The purpose of this study was to determine the magnitude of the influence of price and brand ambassadors on purchase decisions for lipstick products at the official shop on the Shopee marketplace. The type of research chosen by the researcher is Causal Explanatory. The independent variables in this study are product quality, price and brand ambassadors, while the dependent variables is purchasing decisions. Data was collected by distributing questionnaires to female respondents who had bought Madame Gie’s official shop lipstick products in the Shopee marketplace with a total sample of 100 respondents. From the result of the T test, it shows that the price and brand ambassador variables have an effect on purchasing decisions. The influence of the two independent variables on purchasing decisions used in the coefficients of determination formula is 0,397. This means that the effect of price and brand ambassador on purchasing decisions is 39,7%. This research is expected to be input and benefit for the company and further researchers.